(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article is based on revealing the uniqueness of gender-linguistics, one of the modern fields of linguistics, and it examines gender-related forms of reference, stereotypes, as well as gender characteristics of linguistic and cultural units found in literary texts.